2023
DOI: 10.1210/jendso/bvad095
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols May Prevent High-Fat Diet–Induced Dampening of the Hypothalamic–Pituitary–Adrenal Axis in Male Mice

Abstract: Chronic high-fat diet (HFD) consumption causes obesity associated with retention of bile acids (BA) that suppress important regulatory axes, such as the hypothalamic-pituitary-adrenal axis (HPAA). HFD impairs nutrient sensing and energy balance due to a dampening of the HPAA and reduced production and peripheral metabolism of corticosterone (CORT). We assessed whether proanthocyanidin-rich grape polyphenol (GP) extract can prevent HFD-induced energy imbalance and HPAA dysregulation. Male C57BL6/J mice were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Natural polyphenols, including those present in grape pomace, have been shown to improve cognitive function, extend the lifespan, and protect against age-related muscle loss in several mice models (Davinelli & Scapagnini, 2022; Luo et al, 2021; Xu et al, 2021; Ziegler et al, 2023). Studies in mice have shown that grape pomace in the diet can improve metabolic diseases by preventing gut microbiota dysbiosis and increasing the abundance of beneficial taxa (Chacar et al, 2018; Mezhibovsky et al, 2023; Roopchand et al, 2015). In this study, we found that an industrial grape pomace preparation favored the restoration of the physical and non-pathogenic features of biofilms in vitro , potentially indicating the improved resilience of microb-aging communities (Fig.7).…”
Section: Discussionmentioning
confidence: 99%
“…Natural polyphenols, including those present in grape pomace, have been shown to improve cognitive function, extend the lifespan, and protect against age-related muscle loss in several mice models (Davinelli & Scapagnini, 2022; Luo et al, 2021; Xu et al, 2021; Ziegler et al, 2023). Studies in mice have shown that grape pomace in the diet can improve metabolic diseases by preventing gut microbiota dysbiosis and increasing the abundance of beneficial taxa (Chacar et al, 2018; Mezhibovsky et al, 2023; Roopchand et al, 2015). In this study, we found that an industrial grape pomace preparation favored the restoration of the physical and non-pathogenic features of biofilms in vitro , potentially indicating the improved resilience of microb-aging communities (Fig.7).…”
Section: Discussionmentioning
confidence: 99%